Differences in postablation cardiac MRI scar between radiofrequency and cryoballoon ablation: A DECAAF II subanalysis. - Nelson, Daniel Wetherbee; Dhorepatil, Aneesh; Kreidieh, Omar; Mekhael, Mario; Noujaim, Charbel; Assaf, Ala; Feng, Han; Marrouche, Nassir (Journal of Cardiovascular Electrophysiology, 2023)
Introduction: Pulmonary vein isolation (PVI) using radiofrequency (RF) and cryoballoon (Cryo) ablation are standard approaches for rhythm control in patients with symptomatic atrial fibrillation. Both strategies create scars in the left atrium (LA). There have been few studies investigating the difference in scar formation between patients undergoing RF and Cryo using cardiac magnetic resonance (CMR) imaging. Methods: The current study is a subanalysis of the control arm of the Delayed‐Enhancement MRI Determinant of Successful Catheter Ablation of Atrial Fibrillation study (DECAAF II). The study was a multicenter, randomized, controlled, single‐blinded trial that evaluated atrial arrhythmia recurrence (AAR) between PVI alone and PVI plus CMR atrial fibrosis‐guided ablation. Preablation CMR and 3‐ to 6‐month postablation CMR were obtained to assess baseline LA fibrosis and scar formation, respectively. Results: Of the 843 patients randomized in the DECAAF II trial, we analyzed the 408 patients in the primary analysis control arm that received standard PVI. Five patients received combined RF and Cryo ablations, so they were excluded from this subanalysis. Of the 403 patients analyzed, 345 underwent RF and 58 Cryo. The average procedure duration was 146 min for RF and 103 min for Cryo (p =.001). The rate of AAR at ~15 months occurred in 151 (43.8%) patients in the RF group and 28 (48.3%) patients in the Cryo group (p =.62). On 3‐month post‐CMR, the RF arm had significantly more scar (8.8% vs. 6.4%, p =.001) compared to Cryo. Patients with ≥6.5% LA scar (p <.001) and ≥2.3% LA scar around the PV antra (p =.01) on 3‐month post‐CMR had less AAR independent of the ablation technique. Cryo caused a greater percentage of right and left pulmonary vein (PV) antral scar (p =.04, p =.02) and less non‐PV antral scar (p =.009) compared to RF. On Cox regression, Cryo patients free of AAR had a greater percentage of left PV antral scar (p =.01) and less non‐PV antral scar (p =.004) compared to RF free of AAR. Conclusion: In this subanalysis of the control arm of the DECAAF II trial, we observed that Cryo formed a more significant percentage of PV antral scar and less non‐PV antral scar compared to RF. Post ablation LA scar ≥6.5% predicted freedom from AAR, independent of ablation technique. These findings may have prognostic implications in ablation technique selection and freedom from AAR.